Modeling Land Use/Land Cover Change in Berau Pantai Forests, Berau Regency, East Kalimantan Province - Andhi Trisnaputra; Baba Barus; Bambang Hendro Trisasongko (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2023)
Land demands increase with the rise of population and regional development. This results in considerable pressure on forest resources which is characterized by an increasing rate of deforestation. To further explore the impact of deforestation and forest management in regional planning process, this study specifically aimed 1) to identify patterns of land use/land cover changes, 2) to analyze driving factors and 3) to model future land use/land cover. This study employed Landsat imageries to construct land use/land cover maps and their variation across time. Driving factors were analyzed using binary logistic regression. Land use prediction was made through Artificial Neural Network approach. Multitemporal analysis indicated that the research area experienced a decreasing trend of natural forest and shrubs, with substantial extension of existing plantation forests, plantations, agricultural lands and settlements. Indicated driving factors included accessibility, slope class, soil type, forest permit, forest function, RTRW and population density. A forecast in 2030 suggested that natural forests and built-up land would increase from current figures.